Studies in Matthew. By Ulrich Luz. Pp. xii + 385. Grand Rapids, MI: Eerdmans, 2005. isbn 0 8028 3964 9. £18.99/30.00 - Foster, Paul (The journal of theological studies, 2006)
Ulrich Luz's work on the Gospel of Matthew is best known through his magisterial commentary (complete in four volumes in the German EKK series, and recently available in English translation in three volumes, one in the Continental commentary series, the other two in the Hermeneia series—why?) and for his Cambridge volume in the New Testament Theology series. The fruits of his labours on the first Gospel, however, are even more abundant than is suggested by these magisterial works. Readers are now presented with a collection of eighteen studies, many available for the first time in English, which demonstrates the breadth of Luz's reflection on this text across a range of historio-critical, pastoral, and hermeneutical issues.